The People with Arthritis Can Exercise (PACE) Program: A Qualitative Evaluation of Participant Satisfaction - Leigh F. Callahan, PhD; Britta Schoster, MPH; Andrea Meier, PhD; Thelma Mielenz, PT, PhD, OCS; Lisa DiMartino, MPH (Centers for Disease Control and Prevention, 2005)
Introduction Developed by the Arthritis Foundation, People with Arthritis Can Exercise is a community-based exercise program for individuals with arthritis. This qualitative study was designed to assess participant satisfaction with the program and examine motivators and barriers to attending program classes. Methods We conducted an 8-week randomized controlled trial of People with Arthritis Can Exercise among 347 participants residing in 18 urban and rural communities across North Carolina. Semistructured telephone interviews were conducted with 51 of the participants. Participants were asked about their overall satisfaction with the program. Motivating factors and barriers to attending the classes, including content, instructor, location, and schedule, were examined. Results Of the 51 participants interviewed, 96% were female, with an average age in years of 67 (range, 32-90 years). Participants reported deriving considerable social support from exercising in a group with others who have arthritis. They identified two main factors that motivated them to continue participating in the exercise class: ability to work at their own pace during the class and confidence that they could do different kinds of exercise safely. Participants also reported that the instructor played a vital role in sustaining their motivation to exercise. Among the participants, noncompleters of the program reported arthritis-related illness or insufficient physical challenge as key barriers to class participation. Conclusion This study suggests that a group exercise program for older adults with arthritis promotes a sense of social support and increases self-efficacy for exercise by allowing participants to work at their own pace.